Legal Protection For Residents Of The Setia Mekar Residence 2 Cluster Who Were Displaced Based On Decision No. 999 Pk/Pdt/2023 - Sekar Marchayu Setiawan; Atik Winanti (UNIVERSITAS PAKUAN, 2026)
The eviction of the residents of the Setia Mekar Residence 2 Cluster in Bekasi Regency based on Decision Number 999 PK/PDT/2023 has caused legal problems, because the land has now become a settlement inhabited by residents who legally bought houses. This study aims to analyze the basis of the judge's considerations in the decision and examine the legal protection for residents as buyers in good faith. The research uses normative legal methods with three approaches: legislative, case, and conceptual. Data were analyzed qualitatively from primary, secondary, and tertiary legal sources. The results of the study show that the decision is valid and binding as part of a decision with permanent legal force, based on the principle of legal certainty. However, the affected residents are good-faith buyers who buy houses through official procedures. Therefore, legal protection for citizens is focused on recovering losses through the responsibility of developers, both based on treaty law, unlawful acts, and the Consumer Protection Law. Keywords: Eviction, Buyer in Good Faith, Consumer Protection.